Factors That Influence Individual Taxpayer Compliance With Tax Sanctions As A Moderating Variable At The Binjai Pratama Tax Service Office - Epraya Agustina Br. Surbakti; Keulana Erwin; Isfenti Sadalia (Yayasan Multidimensi Kreatif, 2024)
The aim of the research is to determine and analyze the influence of taxpayer awareness, tax knowledge, tax services, tax socialization, and taxpayer financial conditions, on individual taxpayer compliance with tax sanctions as a moderating variable at the Binjai Pratama Tax Service Office. This research was conducted by distributing questionnaires to individual taxpayers registered at the Binjai Pratama Tax Service Office, Binjai City, North Sumatra Province. The sampling method uses probability sampling with an incidental sampling approach, obtaining 100 samples of individual taxpayers from the total population. The analysis method used is SEM-PLS with the help of Smart-PLS software. Hypothesis testing is carried out through a bootstrapping process. The results of the research show that taxpayer awareness and the taxpayer's financial condition have a significant effect on individual taxpayer compliance, however tax knowledge, tax services and tax socialization do not have a significant effect on individual taxpayer compliance at the Binjai Pratama Tax Service Office. Meanwhile, the research results for tax sanctions as a moderating variable are able to moderate taxpayer awareness and tax socialization regarding individual taxpayer compliance at the Binjai Pratama Tax Service Office. However, tax sanctions are unable to moderate tax knowledge, tax services, and the financial condition of taxpayers on individual taxpayer compliance at the Binjai Pratama Tax Service Office